The role of social self-efficacy and psychological capital in IT graduates’ employability and subjective career success - DAO Tung; BUI Thi Thanh Huong (Cogent Social Sciences)
This study aims to assess the impact of Social Self-Efficacy and Psychological Capital on Employability and Subjective Career Success of IT graduates in Vietnam. An empirical research using a questionnaire was carried out from April to August 2022 in big cities in the North and Center of Vietnam. The sample includes 336 university graduates (within 6 years after graduation) who were undertaking IT-related jobs. Research results show that both Social Self-Efficacy and Psychological Capital have a positive impact on Employability and Subjective Career Success (which includes Job Satisfaction and Career Satisfaction). The study’s findings are significant for both educational institutions that offer IT training and human resource management activities for IT staff in organizations and enterprises in Vietnam.